Factors Associated With Off-Label Oncology Prescriptions: The Role of Cost and Financing in a Universal Healthcare System - Gordon, Noa; Goldstein, Daniel A.; Tadmor, Boaz; Stemmer, Salomon M.; Greenberg, Dan (Frontiers in Pharmacology, 2021)
PURPOSE: Various solutions have been put forward for prescribing and reimbursing treatments outside their registered indications within universal healthcare systems. However, most off-label oncology prescriptions are not reimbursed by health funds. This study characterized the financing sources of off-label oncology use and the predictors of the decision to forego treatment. MATERIALS AND METHODS: All 708 off-label oncology requests submitted for approval in a large tertiary cancer center in Israel between 2016 and 2018 were examined for disease and patient sociodemographic characteristics, costs and financing sources, and the factors predicting actual off-label drug administration using multivariate logistic regression analysis. RESULTS: The mean monthly cost of a planned off-label treatment was ILS54,703 (SD = ILS61,487, median = ILS39,928) (approximately US$ 15,500). The main sources of funding were private health insurance (25%) and expanded access pharma company plans (30%). Approximately one third (31%) of the requests did not have a financing source at the time of approval. Of the 708 requests, 583 (or 82%) were filled and treatment was initiated. Predictors for forgoing treatment were the impossibility of out-of-pocket payments or the lack of a financing solution (OR=0.407; p=.005 and OR=0.400; p<.0005). CONCLUSION: Although off-label recommendations are widespread and institutional approval is often granted, a large proportion of these prescriptions are not filled. In a universal healthcare system, the financing sources for off-label treatments are likely to influence access.